Investigating Boron Isotopes for Identifying Nitrogen Sources Supplied by Submarine Groundwater Discharge to Coastal Waters - Tamborski, Joseph; Brown, Caitlin; Bokuniewicz, Henry; Cochran, J. K.; Rasbury, E. T. (Frontiers in Environmental Science, 2020)
Stable isotopes of oxygen, nitrogen, and boron were used to identify the sources of nitrate (NO3–) in submarine groundwater discharge (SGD) into a large tidal estuary (Long Island Sound, NY, United States). Potential contaminants such as manure, septic waste and fertilizer overlap in δ15N and δ18O but have been shown to have distinctive δ11B in non-coastal settings. Two distinct subterranean estuaries were studied with different land-use up gradient, representative of (1) mixed medium-density residential housing and (2) agriculture. These sites have overlapping δ15N and δ18O measurements in NO3– and are unable to discriminate between different N sources. Boron isotopes and concentrations are measurably different between the two sites, with little overlap. The subterranean estuary impacted by mixed medium-density residential housing shows little correlation between δ11B and [B] or between δ11B and salinity, demonstrating that direct mixing relationships between fresh groundwater and seawater were unlikely to account for the variability. No two sources could adequately characterize the δ11B of this subterranean estuary. Groundwater N at this location should be derived from individual homeowner cesspools, although measured septic waste has much lower δ11B compared to the coastal groundwaters. This observation, with no trend in δ11B with [B] indicates multiple sources supply B to the coastal groundwaters. The agricultural subterranean estuary displayed a positive correlation between δ11B and [B] without any relationship with salinity. Binary mixing between sea spray and fertilizer can reasonably explain the distribution of B in the agricultural subterranean estuary. Results from this study demonstrate that δ11B can be used in combination with δ15N to trace sources of NO3– to the subterranean estuary if source endmember isotopic signatures are well-constrained, and if the influence of seawater on δ11B signatures can be minimized or easily quantified.